Analisis Studi Kasus Mengenai Usia Ibu dan Gambaran Fisik Penderita Sindrom Down - Arvanda, Diela Gista; Izzah, Annisa Nurul (JURNAL BIOSENSE, 2023)
Down syndrome or trisomy 21 is the most common genetic disorder among other genetic disorders. The definition of Down syndrome is a chromosomal abnormality in which there is an extra copy of chromosome 21 due to non-disjunction, mosaicism or the rarest occurrence is translocation. The age of the mother when pregnant is one of the factors causing Down syndrome, the older the mother's age, the greater the chance of Down syndrome. The development of Down syndrome children is different from other normal children, so special care and parenting are needed. The purpose of this research is to analyze through case studies of Down syndrome patients aspects of birth occurrence, aspects of child growth and development, and aspects of the physical description of Down syndrome patients. The results of this study indicate that many factors can influence the occurrence of Down syndrome, namely genetic factors, radiation factors, and the age of the mother. If Down syndrome children receive a form of therapy, health care, and supportive parenting and environment. Then Down syndrome children can adapt well such as how to communicate and interact.